Perancangan dan Pendampingan Pembangunan Mushola Tahan Gempa di Desa Mekarlaksana, Kabupaten Cianjur - Syahriyah, Dewi Rachmaniatus; Novis Putri, Tika; Septian , Ridho; Dira Nur Azizah (Jurnal Pengabdian Tri Bhakti, 2024)
Community service was performed by planning and helping to build the Al Barokah Prayer Room, an earthquake-resistant prayer space located in Mekarlaksana Village, Cianjur Regency. As a specialist, Abdimas implements the plan and facilitates communication amongst construction workers. The purpose of this support is to ensure that the Al Barokah Prayer Room is built in compliance with the Technical Work Implementation Plan, both in terms of construction length and design. In order to maximize finance and time efficiency, a hybrid approach utilizing Whatsapp media was used for design and development support in this project. When this technology is used effectively, it facilitates coordination between field implementers, foundations, and community services, allowing for the proper handling of issues and the quick fixes that are required. In terms of coordination, supervision, problem-solving, and timeliness, the result is the realization of the design and construction of an earthquake-resistant prayer room by qualified architects and construction experts in Mekarlaksana Village, Cianjur Regency.